Differences in brain activity during motor imagery of shotput between the whole- and part-training methods - Miayuchi, I.; Nakagawa, K.; Iso, S. (Scientific Journal of Sport and Performance, 2025)
We compared the differences between the brain regions activated during motor imagery using the whole-training and part-training methods and focused on how brain-activation patterns vary depending on athletes` individual characteristics. We included four throwing athletes with varying levels of competitive ability and shotput specialization, including elite athletes who attained upper ranks in the Japan Championships. The experimental tasks included motor imagery of a complete shotput attempt (whole method) and standing throw excluding the glide phase (part method). Functional magnetic resonance imaging was used to measure brain activity during these tasks. The results showed that individual variations in the brain regions were activated by both the whole and part methods. Regarding the inter-individual differences between the whole and part methods, in one high-level athlete, more brain regions, including the frontal lobe, were activated in the whole method compared to the part method. For athletes with lower competitive levels or specialization, no significant difference in brain activity was observed between the motor imagery of the whole and part methods. Thus, there are inter-individual differences in the brain regions that are activated during whole- and part-training methods and these vary depending on the athletes` competitive ability and specialization.